RNA binding protein DDX5 directs tuft cell specification and function to regulate microbial repertoire and disease susceptibility in the intestine. Issue 9 (1st December 2021) - Long, Tianyun; Abbasi, Nazia; Hernandez, Juan E; Li, Yuxin; Sayed, Ibrahim M; Ma, Shengyun; Iemolo, Attilio; Yee, Brian A; Yeo, Gene W; Telese, Francesca; Ghosh, Pradipta; Das, Soumita; et al.
Abstract : Objective: Tuft cells residing in the intestinal epithelium have diverse functions. In the small intestine, they provide protection against inflammation, combat against helminth and protist infections, and serve as entry portals for enteroviruses. In the colon, they had been implicated in tumourigenesis. Commitment of intestinal progenitor cells to the tuft cell lineage requires Rho GTPase Cell Division Cycle 42 (CDC42), a Rho GTPase that acts downstream of the epidermal growth factor receptor and wingless-related integration site signalling cascades, and the master transcription factor POU class 2 homeobox 3 (POU2F3). This study investigates how this pathway is regulated by the DEAD box containing RNA binding protein DDX5 in vivo. Design: We assessed the role of DDX5 in tuft cell specification and function in control and epithelial cell-specific Ddx5 knockout mice (DDX5 ΔIEC ) using transcriptomic approaches. Results: DDX5 ΔIEC mice harboured a loss of intestinal tuft cell populations, modified microbial repertoire, and altered susceptibilities to ileal inflammation and colonic tumourigenesis. Mechanistically, DDX5 promotes CDC42 protein synthesis through a post-transcriptional mechanism to license tuft cell specification. Importantly, the DDX5-CDC42 axis is parallel but distinct from the known interleukin-13 circuit implicated in tuft cell hyperplasia, and both pathways augment Pou2f3 expression in secretory lineage progenitors. In mature tuft cells, DDX5 not only promotes integrin signalling and microbial responses, it also represses gene programmes involved in membrane transport and lipid metabolism. Conclusion: RNA binding protein DDX5 directs tuft cell specification and function to regulate microbial repertoire and disease susceptibility in the intestine.